Some Topological and Polynomial Indices (Hosoya and Schultz) for the Intersection Graph of the Subgroup ofã€– Zã€—_(r^n ) - Nawaf, Alaa J.; Mohammad, Akram S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Let  be any group with identity element (e) . A subgroup intersection graph of  a subset  is the Graph with V ( ) =  - e and two separate peaks c and d contiguous for c and d if and only if      , Where  is a Periodic subset of resulting from  . We find some topological indicators in this paper and Multi-border (Hosoya and Schultz) of   , where    ,  is aprime number.